Appropriate Technology Sourcebook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Appropriate technology sourcebook / Darrow. K. and M. Saxenian. 1986. Volunteers in Asia, Stanford. 800 pp. ISBN 0 917704 17 7